L-triiodothyronine stimulates growth by means of an autocrine factor in a cultured growth-hormone-producing cell line. - Miller, M J (1987)
L-Triiodothyronine (T3) stimulates DNA synthesis and replication of cultured GC cells, a T3-responsive growth hormone (GH)-secreting cell line. To determine whether T3 stimulates secretion of an autocrine growth factor, we compared the growth-promoting activity of medium conditioned by T3-stimulated and T3-depleted cells to that of unconditioned medium. Addition of polyclonal rabbit anti-T3 serum to T3-containing media decreased cellular T3 content by 50-70%. In unconditioned medium, anti-T3 serum decreased T3-induced cell growth and GH production by 40-70%. In conditioned medium, anti-T3 serum also effected a 45-70% decrease in induction of GH secretion but did not attenuate the growth-promoting activity. Growth-promoting activity was not detected in medium conditioned by T3-depleted cells. Thus, conditioned medium from T3-containing GC cell cultures contains growth-promoting activity that is independent of T3. Further, the induction of GC cel growth by T3 may occur, at least in part, by induction of an autocrine growth factor.